An analysis of a DGS‐inserted stub resonator and its application to an optimum BSF. Issue 5 (8th April 2018) - Shin, Imseob; Oh, Sangyeol; Lee, Changwon; Kwon, Koohyung; Kim, Young‐Sik
Abstract: A novel defected ground structure (DGS)‐inserted stub (DIS) resonator is proposed. The proposed DIS resonator features a typical dumbbell‐shaped DGS inserted into an conventional open‐circuited stub (OCS) resonator, and it is modeled by a series LC resonator. The inserted DGS can suppress a harmonic and extend an upper passband. Therefore, the proposed DIS resonator to generate a resonance at 2.0 GHz keeps the upper passband up to 8.0 GHz or higher, while the OCS resonator with the same resonance gives rise to the harmonic at 5.78 GHz. These properties are investigated through EM simulation. Moreover, in order to verify the applicability of the proposed DIS resonator to microwave filters, two optimum bandstop filters (BSFs) with the same stopband at 2.0 GHz using the proposed DIS and OCS resonators are fabricated and measured, respectively. Compared to the optimum BSF using the OCS resonator, the optimum BSF using the proposed DIS resonator shows two notable improvements: a 50% increase in the upper passband and a 15% reduction in the size.